HUMAN CONCEPT AND MOTIVATION IN BEHAVIOR PSYCHOLOGICAL AND ISLAMIC PERSPECTIVE - Makki, Ali (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Humans consist of physical and psychological structures that have a variety of effective functions in behavior. Motivation is an important thing for moving the human body's organs in the activity. Human activity generally can be driven by everything in him selfs so that it’s can make the personality of human behavior as well as external influences from the environment, whether in positive or negative behavior. In this discussion, the motivation for making behavior in the realm of psychology and Islamic education is creating the formation of good human character (akhlak al-karimah) on religious and social aspects. Humans can be said to have good behavior if the motivation they generate is also good and otherwise. So, one important thing in the formation of behavior is continuously motivation within humans, so that they become perfect humans in the future and get a position as respectable humans while aplicating the main of human responsibilities.